Post Exposure Prophylaxis for HIV in the sexual exposure scenario (PEPSE): Development of a novel nanoformulation - Sanders Velez, Carlos/ CSV (2022)
Since the year 2012, 2 million newly diagnosed cases of human immunodeficiency virus (HIV) have been found every year. Prevention schemes based on condoms, and other pharmacological interventions such as post exposure prophylaxis in a sexual exposure scenario (PEPSE) have had positive impact in the pandemic. Under current PEPSE guidelines due to risk to benefit ratios, only high-risk unprotected sexual events (>1/1000) are prescribed antiviral prophylaxis. Such a situation leaves a population unprotected, whose size is unknown, that is in a low to moderate risk of HIV acquisition. To assess the size and views of a population that is currently unprotected by current prevention schemes, two online survey studies were set up in Thailand and the UK (Chapter 2). Both questionnaires were designed to probe for unplanned low to moderate risk of sexual exposure to HIV. Both data sets were analysed through demographic statistics and logistic regression to assess for unsafe intercourse. The results suggest that the proportion of the population reporting unplanned unsafe sexual intercourse events is as high as 29.1% in the UK study and 15.8% in the study in Thailand. Such a high proportion of sexually active population presents a target for further alternative prevention schemes and a research priority. One such alternative prevention scheme would be a localised (anal or vaginal delivery) nanoparticle drug delivery system, with high drug content, targeting local lymphatic nodes (Chapter 3). Dolutegravir (DTG) was chosen as the model antiretroviral agent due to its favourable side effect profile, high genetic barrier and high antiviral potency. However, the physiochemical properties of DTG such as its hydrophilicity are a challenge for the entrapment of DTG under traditional nanoformualtions. A DTG prodrug, dolutegravir myristate (MDTG) was synthesized based on Sillman et al. to generate a high drug content formulation, a two-step solvent displacement experimental set up was designed. The first step was designed to formulate a MDTG nanocrystal emulsion, and the second step was designed to coat the nanocrystal with a minimal mass of a polymeric nanocarrier. The formulation developed through a coating method has a fast release of compound, as 100% of the payload gets released before 2 hours. This work provides evidence that a substantial percentage of the sexually active population, may find themselves in an unplanned low to moderate risk scenario for sexual HIV acquisition. A potential solution for this population may lie in a localised nanoparticle delivery system to the vaginal or anal tissue (Chapter 4). In this work, proof of concept of coating an MDTG nanocrystal for this purpose was achieved. However, the drug release profile is not ideal for PEPSE purposes, thus future research is needed to perfect such a delivery system.